2010
DOI: 10.1016/j.virol.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo depletion of CD4+CD25hi regulatory T cells is associated with improved antiviral responses in cats chronically infected with feline immunodeficiency virus

Abstract: Regulatory T (Treg) cells are activated and suppress immune responses during infection, and are characterized as CD4+CD25hiFOXP3+. Ex vivo studies demonstrate that Treg cells potentially suppress anti-HIV-1 T cell responses. Lentivirus-induced CD4+CD25hi Treg cells were first described in feline immunodeficiency virus (FIV)-infected cats. In the present study we demonstrate that anti-feline CD25 monoclonal antibody (mAb) therapy depletes Treg cells in FIV-infected cats for four weeks and does not exacerbate vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…During chronic FIV, SIV or HIV-1 infection it is clear that Treg cells suppress antiviral responses in vitro [10], [12], [13], [14]. We have shown that this suppression is also exerted in vivo during chronic FIV infection [18]. Whether the net effect of suppressing chronic immune activation is beneficial likely depends on the immunologic and virologic set-point of any given individual.…”
Section: Discussionmentioning
confidence: 82%
“…During chronic FIV, SIV or HIV-1 infection it is clear that Treg cells suppress antiviral responses in vitro [10], [12], [13], [14]. We have shown that this suppression is also exerted in vivo during chronic FIV infection [18]. Whether the net effect of suppressing chronic immune activation is beneficial likely depends on the immunologic and virologic set-point of any given individual.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, when Tregs of FIV-infected cats were depleted in vivo, anti-FIV immune responses were improved. 41 As in cats, Foxp3 þ Tregs in cattle increase in blood after infection with bovine leukemia virus. 80 Similar findings have been shown in other species.…”
Section: Tregs and Infectious Diseasesmentioning
confidence: 99%
“…Finally, the ability of the immune system to adequately respond and kill reactivated cells is critical to proposed strategies to purge viral reservoirs. Selective depletion of CD4 + CD25+ cells has been shown to result in improved antiviral responses in cats chronically infected with FIV [83,86], which could potentially be part of a strategy to boost the immune system during or after ALT. There is much still to be learned about these and other interactions between the immune system and latent FIV.…”
Section: Reviewmentioning
confidence: 99%